PENGARUH MOTIVASI DAN DISPLIN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA JAMBULUWUK OCEANO SEMINYAK HOTEL - I Made Windu Windika; I Nengah Aristana (Journal Research of Management, 2020)
Employees are the main assets in running a company's operations. The problem raised in this study is motivation (X1) influences performance (Y) in Jambuluwuk Oceano Seminyak Hotel, how does work discipline (X2) affect performance (Y) in Jambuluwuk Oceano Seminyak Hotel, how much is the influence of work motivation and work discipline on employee performance at Jambuluwuk Oceano Seminyak Hotel and which independent variables have a dominant influence on employee performance at Jambuluwuk Oceano Seminyak Hotel. The population in this study amounted to 94 people. This study uses the population as a sample. The data analysis technique used is multiple linear regression analysis. The results of the analysis show a regression model Y = 4,510 + 0,246 (X1) + 0,285 (X2) The conclusion obtained is Motivation (X1) has a positive influence on employee performance at the Jambuluwuk Oceano Seminyak Hotel as indicated by the positive coefficient b1X1 regression coefficient. Work discipline (X2) has a positive influence on employee work discipline at the Jambuluwuk Oceano Seminyak Hotel, this can be seen in the positive coefficient b2X2 which is positive. The magnitude of the effect of motivation and work discipline on employee performance at Jambuluwuk Oceano Seminyak Hotel was 43.6% and the remaining 56.4% was influenced by other variables not examined in this study. The independent variable that has a dominant influence on Employee Performance is the work discipline variable (X2) that is equal to 0.285 while the Motivation variable (X1) is 0.246